Human macrophage model for selective evaluation of CD8⁺ and γδ⁺ cytotoxic T cell function in tuberculosis - Passmore, Jo-Ann Shelley (Department of Medicine, 2018)
The human macrophage cell line U937 was investigated as an in vitro model for human macrophage function in mycobacterial infections. This involved evaluating the ability of differentiated U937 cells to phagocytose Mycobacterium tuberculosis, control intracellular mycobacterial growth, and present mycobacterial antigens to human HLA class I-matched cytotoxic T lymphocytes (CTLs). Differentiation of U937 cells usmg IFN-γ, 1,25-(OH)₂ vitamin D₃, or PMA significantly enhanced their ability to phagocytose M. tuberculosis but failed to induce a subsequent respiratory burst response. Following infection, U937 cells were found to be permissive to the intracellular growth of both the virulent H37Rv strain of M. tuberculosis and the attenuated vaccine strain of M. bovis BCG. U937 cells have been shown to constitutively express high levels of cell surface HLA class I while expressing undetectable levels of HLA class II both at the mRN A level and at the cell surface. HLA class II expression was neither up-regulated following infection with M. tuberculosis nor inducible using IFN-γ, 1,25-(OH)₂ vitamin D₃, PMA, GM-CSF or a combination of these agents. In contrast, chronic infection of U937 cells with virulent H37Rv M. tuberculosis (but not with BCG) resulted in the cell surface expression of HLA class I being significantly up-regulated. Taken together, these characteristics made U937 cells a very attractive model for further investigations into their ability to present mycobacterial antigens to human HLA class I-restricted CTLs. Differentiation of U937 cells was found to completely abrogate their sensitivity to non-antigen specific cytolysis mediated by NK or LAK cells. Following infection with M. tuberculosis, U937 target cells were lysed by M. tuberculosis-primed CTLs from HLA class I-matched donors in an antigen-specific manner and with a similar efficiency to autologous macrophage targets. This cytolytic activity was restricted to live organisms since only U937 cells infected with virulent H37Rv M. tuberculosis and BCG but not those pulsed with soluble PPD were lysed by the HLA class I-matched effector cells. On the other hand, M. tuberculosisstimulated but ALA-mismatched CTLs failed to lyse infected U937 cells in an antigen-specific manner. T cell subset fractionation of the HLA class I-matched M. tuberculosis-primed CTL population and limiting dilution cloning demonstrated that the cytolytic activity was mediated by CD8⁺ cytolytic T cells and confirmed that CD4⁺ T cells showed no significant ability to lyse infected U937 target cells. Furthermore, this study found that M. tuberculosis-infected U937 target cells were lysed by CD8⁺ CTLs more rapidly and strongly than similarly infected autologous macrophage targets demonstrating the sensitivity of this in vitro model as an indicator for CD8⁺ cytolytic function in mycobacterial infections. M. tuberculosis-infected U937 cells were found to be highly sensitive to mycobacterial antigenspecific cytolysis mediated by γδ⁺ CTL. Mycobacterial antigen-specific γδ⁺ CTLs consistently showed stronger cytolytic activity against infected U937 target cells than γδ⁺ CTL but were not restricted to classical HLA class I or class II molecules. A panel of cytolytic human M. tuberculosis-reactive γδ⁺ CTL clones was established to investigate more thoroughly the role of γδ⁺ CTL lytic activity in human mycobacterial infections. This study examined the mechanism of cellular cytotoxicity used by these mycobacterial-specific γδ⁺ CTL clones against infected U93 7 targets and further investigated the effect of γδ⁺ T cell-mediated cytolysis on intracellular mycobacterial survival. Cytolysis mediated by the γδ⁺ T cell clones was found to be dependent on cell-to-cell contact. Furthermore, the ability of the γδ⁺ CTL clones to lyse infected targets was found to be strongly Ca²⁺-dependent, sensitive to cyclosporine A (a specific inhibitor of granule exocytosis ), and completely abrogated following Sr²⁺-induced de-granulation of the γδ⁺ T cell effectors, indicating that cytoxicity was mediated predominantly by the granule exocytosis/ perforin pathway. Despite being strongly cytolytic against infected U937 cells, however, the γδ⁺ CTL clones did not have any impact on the survival of intracellular M. tuberculosis. The major conclusions of this study are that U937 cells not only provide a useful in vitro human macrophage model allowing for selective evaluation of HLA class I-restricted CD8⁺ CTL function in mycobacterial infections but also provided a highly sensitive indicator for γδ⁺ CTL cytolytic activity.